Education Students' Stigma Toward Mental Health Problems: A Cross-Cultural Comparison - Gallego, José; Cangas, Adolfo J.; Aguilar, José M.; Trigueros, Rubén; Navarro, Noelia; Galván, Blanca; Smyshnov, Konstantin; Gregg, Melanie (Frontiers in Psychiatry, 2020)
One of the main obstacles to integrating individuals with severe mental disorders into society today is the stigma directed at them. Although breakthroughs in treatment have been made in recent years, many professionals continue to admit that they do not possess enough training to combat this problem. Considering this situation, the present study analyzes the existing stigma among University Education students in three countries with different education systems and cultures, namely Spain, Russia and Canada. A total of 1542 students from these three countries participated in the study. The results showed that the highest rates of stigma were in Spain and the lowest were in Canada, while Russia displayed intermediate values. This study highlights the importance of these results and the need to train Education students and professionals in the education field through awareness programs and campaigns which may serve as an effective strategy for reducing the stigmatization of people with mental disorders.